Comparative growth performance of major and minor carps of genus Labeo in lesser Himalayan region, India - MISHRA, ASHUTOSH; SHARMA, LOVEDEEP (The Indian Journal of Animal Sciences, 2025)
To evaluate the growth performance of Indian major carps (Labeo catla and Labeo rohita) and minor carp (Labeo gonius) in captivity, an experiment was conducted for 90 days. Three different treatment sets (T1, T2, and T3) in FRP tanks (Size. 2.5 m diameter with 4 m3 water volume) in triplicate with experimental fishes (L. catla, L. rohita and L. gonius) @ 25 fingerlings m-3 with uniform combinations of 1:1 (T1- L. catla and L. gonius; T2- L. catla and L. rohita, T3- L. rohita and L. gonius) were maintained indoor in polycarbonate house. Throughout experimental period, growth parameters viz. weight gain, length gain and specific growth rate were observed. In addition, important water quality parameters viz. water temperature, total dissolved solids, conductivity, dissolved oxygen and pH were recorded fortnightly and found to be optimum. The statistical analysis showed a significant difference in the weight gain of experimental fish among treatments. The highest weight gain was observed in the experimental fishes of treatment T1 compared to T2 and T3 treatments. The specific growth rate ranged between 0.1 to 0.35% per day. A significant difference in fish survival rate was observed among treatments in which T1 and T3 showed better survival than T2. Overall results showed that the growth performance of L. gonius in combination with L. catla was best among all while L. gonius performed excellent with L. catla. The findings of work could provide valuable insights into the development of improved composite aqua farming practices leading to enhanced production and economic upliftment.